Strategies for improving teachers' pedagogical competence in Dinas Pendidikan Kota Palangka Raya - Hapijah Hapijah; Siminto Siminto; Sapuadi Sapuadi (Himpunan Pengembang Kurikulum Indonesia, 2025)
Improving teacher competence is a top priority for Dinas Pendidikan Kota Palangka Raya in creating human resources that are superior, professional, and adaptive to the times. This study aims to determine the strategies employed by Dinas Pendidikan Kota Palangka Raya to enhance teachers' pedagogical competence, encompassing the planning, implementation, monitoring, and evaluation stages. The research employed a qualitative approach, utilizing data collection techniques that included interviews, observation, and documentation. The research subjects consisted of the heads of the education and teaching staff sections, administrators, and staff in the field of personnel development and education data management. The study's results indicate that planning is conducted through the development of APBD-based training programs that encompass all levels of education. Implementation is realized through workshops, training, and the use of information technology in collaboration with universities and Google for Education. Monitoring and evaluation are conducted routinely through observation, performance assessments, and feedback from teachers. Obstacles such as time constraints and technological limitations of some teachers are overcome through online training and mentoring. This program has a positive impact on improving teacher professionalism and equalizing the quality of education in Palangka Raya City. Abstrak Peningkatan kompetensi guru merupakan prioritas utama Dinas Pendidikan Kota Palangka Raya dalam menciptakan sumber daya manusia yang unggul, profesional, dan adaptif terhadap perkembangan zaman. Penelitian ini bertujuan untuk mengetahui strategi Dinas Pendidikan Kota Palangka Raya dalam meningkatkan kompetensi pedagogik guru yang mencakup tahap perencanaan, pelaksanaan, serta monitoring dan evaluasi. Metode penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Subjek penelitian terdiri atas kepala seksi pendidik dan tenaga kependidikan, pengelola, serta staf bidang pembinaan ketenagaan dan pengelolaan data kependidikan. Hasil penelitian menunjukkan bahwa perencanaan dilakukan melalui penyusunan program pelatihan berbasis APBD yang mencakup seluruh jenjang pendidikan. Pelaksanaan diwujudkan melalui workshop, pelatihan, dan pemanfaatan teknologi informasi bekerja sama dengan perguruan tinggi serta Google for Education. Monitoring dan evaluasi dilakukan secara rutin melalui observasi, penilaian kinerja, dan umpan balik dari guru. Hambatan seperti keterbatasan waktu dan kemampuan teknologi sebagian guru diatasi melalui pelatihan daring dan pendampingan. Program ini berdampak positif terhadap peningkatan profesionalisme guru dan pemerataan kualitas pendidikan di Kota Palangka Raya. Kata Kunci: evaluasi program pembelajaran; kompetensi guru; evaluasi program pembelajaran